The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1111/j.1432-1033.1997.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐Specific Expression of Promoter Regions of the αr1(VI) Collagen Gene in Cell Cultures and Transgenic Mice

Abstract: Cis-acting regions regulating transcription of the alpha1(VI) collagen chain have been investigated in vitro by transfection of promoter-CAT (where CAT is chloramphenicol acetyltransferase) constructs in different types of cultured cells and in vivo in transgenic mice carrying the same CAT constructs or minigenes derived from the fusion of genomic and cDNA sequences in which small deletions of the collagenous domain had been engineered. 215 bp of 5'-flanking sequence showed promoter activity in vitro, yet were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(16 reference statements)
0
10
0
1
Order By: Relevance
“…Although, as stated above, no locus control regions have been defined yet, a correspondence between hypersensitive sites and actual transcription has been found also for collagen genes, in particular ␣2(I) and ␣1(I) (5,11). As for the manner in which the different cis-acting regulatory elements contribute to the transcriptional regulation of a collagen gene, the available data suggest that they act in a modular way (4,5,12,13). As proposed recently by Arnone and Davidson (14), this means that each region contributes "a particular regulatory function that is a subfraction of the overall combined regulatory function executed by the complete system" independently from the other regions.…”
mentioning
confidence: 99%
“…Although, as stated above, no locus control regions have been defined yet, a correspondence between hypersensitive sites and actual transcription has been found also for collagen genes, in particular ␣2(I) and ␣1(I) (5,11). As for the manner in which the different cis-acting regulatory elements contribute to the transcriptional regulation of a collagen gene, the available data suggest that they act in a modular way (4,5,12,13). As proposed recently by Arnone and Davidson (14), this means that each region contributes "a particular regulatory function that is a subfraction of the overall combined regulatory function executed by the complete system" independently from the other regions.…”
mentioning
confidence: 99%
“…Finally, the sequence between about Ϫ5.4 to Ϫ3.9 kb from the transcription start site contains information for expression in articular cartilage, intervertebral disks, nerves, vibrissae, and subepidermal mesenchyme. The strong activating capacity of the Ϫ5.4-to Ϫ3.9-kb sequence has been confirmed by experiments with transgenic mice, where promoter-CAT fusions including this region are expressed in several tissues over 100 times more efficiently than constructs lacking it (9). One interesting feature of the Ϫ5.4/Ϫ3.9 region is that information controlling transcription in cells with different embryological origin and function, including articular chondrocytes, Schwann cells, 2 and fibroblasts, is enclosed in a relatively small DNA fragment, 1.5 kb, a size compatible with that of a single enhancer (11).…”
mentioning
confidence: 77%
“…C2C12 myoblasts were not used in this experiments because we had previously demonstrated that there is no significant difference of CAT expression between p1.4(A-P)CAT and p1.4CAT (9). On the contrary, the whole enhancer region increased transcription considerably in NIH3T3, MC615, and sternal chondroblasts from chick embryos (Fig.…”
Section: Transient Transfections With Deletions Of the ϫ54/ϫ39 Regionmentioning
confidence: 99%
See 2 more Smart Citations